Die andere Möglichkeit. Un’annotazione su tecnica e possibilità - Ardovino, Adriano (Mechane, 2022)
Starting from the relationship between technology and possibility, the article examines the concept of Möglichkeit in Heidegger’s Being and time in order to propose a different interpretation of the “other possibility”, which Heidegger evokes in the famous lecture The question concerning technology.